2020
DOI: 10.3390/ijms21124447
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dominant KCNQ2 Exon 7 Partial In-Frame Duplication in a Complex Epileptic and Neurodevelopmental Delay Syndrome

Abstract: Complex neurodevelopmental syndromes frequently have an unknown etiology, in which genetic factors play a pathogenic role. This study utilizes whole-exome sequencing (WES) to examine four members of a family with a son presenting, since birth, with epileptic-like crises, combined with cerebral palsy, severe neuromotor and developmental delay, dystonic tetraparexia, axonal motor affectation, and hyper-excitability of unknown origin. The WES study detected within the patient a de novo heterozygous in-frame dupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Written informed consent for the genomic study was obtained from both parents. Research protocol and consent forms were approved by the Institutional Review Boards of Hospital Universitario de Salamanca-Centro de Investigación del Cancer as reported in a previous publication [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Written informed consent for the genomic study was obtained from both parents. Research protocol and consent forms were approved by the Institutional Review Boards of Hospital Universitario de Salamanca-Centro de Investigación del Cancer as reported in a previous publication [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is likely that heterogeneity in neurological phenotypes can also be a consequence of alternative combinations of genetic changes in genes associated to cellular functions that are involved in the phenotype and constitute the individual variome [ 8 , 9 ]. Therefore, we tested this hypothesis by searching for CNV variome differences among the four family members of a complex case of a child, as test case, that presented a developmental and epileptic encephalopathy of neonatal onset that has a novel KCNQ2 mutation resulting from a partial KCNQ2 exon 7 duplication that impairs its inhibitory signal [ 17 ] and to determine if the proband has a CNV pattern associated to neuronal functions. However, the complexity of the neurological syndrome suggested that, although this mutation is necessary, there has to be additional cooperating genetic alterations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the WES study did not identify any additional gene variant or mutant associated to the pathology, in addition to the known KCNQ2 exon 7 partial duplication [17], and in order to detect additional cooperating gene alterations that contribute to the pathogenesis of the patient complex neurological syndrome, the genome of the proband and family members was further studied by SNP microarrays to detect CNVs.…”
Section: Cooperating Cnvs In Neuro-pathogenic Genesmentioning
confidence: 99%
“…Intronic alterations can alter the processing of the RNA or its stability. Calcium-dependent celladhesion protein primarily expressed in the developing brain [73,74] PCDH19 pathogenic variants and CNV in epilepsy [38,[73][74][75][76][77][78] Next, we performed a search for a pathogenic association of all the genes comprised within these CNVs detected in the patient, by either SNP microarray or WES, and correlated their functions with different aspects of the clinical phenotype [17]. For this aim the VarElect program was used [22].…”
Section: Cooperating Cnvs In Neuro-pathogenic Genesmentioning
confidence: 99%